Women’s right to marry under Fiqh al-Hanafi: appraisal on the impact of Hanafis’s view on marriage without wali in Malaysia - Mohd, Azizah; Ibrahim, Badruddin; Abd Razak, Syafiqah (LexisNexis, 2019)
Pillars of marriage under the Hanafi and Shafi’i Mazhab differs in the sense that under Fiqh al-Hanafi, guardian is not one of the pillars of marriage. Meanwhile, the Shafi’is are of the view that guardian is one of the pillars of marriage. In Malaysia, women’s right to marry is based on Shafi’I school of law. Therefore, before a woman may get married, consent of a guardian is essential, the absence of which will render the marriage to be invalid. The problem arises in the case where the guardian particularly wali nasab refuses to consent, where in this case the daughter will resort to fiqh al-Hanafi and contract the marriage without the consent of wali nasab. The issue that further arises is the question of validity of such marriage and the status of children legitimacy that is born out of such marriage under Malaysian law. This paper deals with women’s right to marry under fiqh al-Hanafi. The research examines the provisions of Islamic Family law (Federal Territories) Act 1984 on wali and several decided cases relating to marriage solemnized without the presence of the wali. The study adopts qualitative research analysis and is basically library research. It is believed that the findings of the research will be beneficial to all students, academics, researchers, legal practitioners and the public as a whole.